2011
DOI: 10.3896/ibra.4.03.1.08
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tualang honey in comapison to silver in dressing wounds in rats

Abstract: Tualang honey is obtained from large honeycombs produced by Asian bees (Apis dorsata) in gigantic Tualang trees. It has been used traditionally by local communities to treat wounds. However, unlike manuka honey its medicinal uses are not well researched. An open, prospective study into the efficacy of wound healing in full thickness wounds in rats, was designed to compare two honey impregnated dressings with silver-impregnated hydrofibre dressings. A full-thickness wound was created on the dorsum of Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“… 30 and Zaharil et al. 31 respectively studied the effect of Tualang honey on full-thickness wounds in Sprague Dawley rats. Sukur et al.…”
Section: Discussionmentioning
confidence: 99%
“… 30 and Zaharil et al. 31 respectively studied the effect of Tualang honey on full-thickness wounds in Sprague Dawley rats. Sukur et al.…”
Section: Discussionmentioning
confidence: 99%
“…Honey contains glucose, fructose, amino acids, bio-enzymes multi-vitamins and multi-minerals [7]. It is reported that honey has antioxidant, anti-inflammatory, antimicrobial and anti-tumor properties [4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Honeymentioning
confidence: 99%
“…Preparat yang sudah diwarnai dengan HE ke mudian diamati dengan menggunakan mikros kop cahaya menggunakan pembesaran 400 kali dan kemudian dibuat foto preparat yang dibagi dalam tiga lapang pandang. Penilaian pemben tukan kelenjar keringat dibuat dalam scoring yaitu: (1) jumlah kelenjar sebasea sedikit (1-10/ hpf), (2) jumlah kelenjar sebasea cukup banyak (11-20/hpf), (3) jumlah kelenjar sebasea tampak banyak (>20/hpf) [12].…”
Section: Pengamatan Pembentukan Kelenjar Sebaseaunclassified